All-carbon [3 + 2] cycloaddition in natural product synthesis - Wang, Zhuo; Liu, Junyang (Beilstein Journal of Organic Chemistry, 2020)
Many natural products possess interesting medicinal properties that arise from their intriguing chemical structures. The highly-substituted carbocycle is one of the most common structural features in many structurally complicated natural products. However, the construction of highly-substituted, stereo-congested, five-membered carbocycles containing all-carbon quaternary center(s) is, at present, a distinct challenge in modern synthetic chemistry, which can be accessed through the all-carbon [3 + 2] cycloaddition. More importantly, the all-carbon [3 + 2] cycloaddition can forge vicinal all-carbon quaternary centers in a single step and has been demonstrated in the synthesis of complex natural products. In this review, we present the development of all-carbon [3 + 2] cycloadditions and illustrate their application in natural product synthesis reported in the last decade covering 2011–2020 (inclusive).
Keywords: all-carbon; cyclization; [3 + 2] cycloaddition; natural product synthesis; stereocenters